The irruption of social media in crisis communication - Martínez Rolán, Xabier (Estudios sobre el Mensaje Periodístico, 2012)
Social media have strongly irrupted in our society. This is about new interaction channels that split up with the classical communication paradigm. In the field of business communication the emergence of social media has allowed certain components to make sense of the communication process, like feedback. Social networks let companies to start dialogues with their audiences, so social media management gets vital significance, especially in those moments, like crises, that are more sensitive to the entities. This article provides guidelines for crisis management in social media, from the analysis of business communication errors in social networks.
Keywords: social media; crisis; management; communication; online; social networks.